AN ANALYSIS OF THE IMPLEMENTATION OF COMPREHENSIVE SEXUALITY EDUCATION IN SCHOOLS JUNIOR AND SENIOR HIGH SCHOOL - Nahda Fini; Patricia Agustina; Jasmine Winasti; Fathiyah Mumtaz (STIKes Karsa Husada Garut, 2023)
Introduction: Through that conditions for the implementation of CSE in the world, we aimed to analyze the implementation of CSE in secondary school and provide recommendations to improve implementation of CSE. Methods: The method used in the research was a literature study using nine articles that had been selected based on inclusion and exclusion criteria which were then analyzed through assessment and critical evaluation. Result: The result of the literature review of 9 articles is that there us a significant relationship between comprehensive sexuality education with knowledge, attitude, self- efficacy, risk sexual behavior, condom use, and decision making in students in secondary school. In addition, there are also inhibiting factors in providing comprehensive sexual education, namely the lack of communication between parents and adolescent about sexual problems due to cultural taboo and shame. Conclusions: Comprehensive Sexuality Education is one effective strategy that can be done to prevent the negative impact of risky behaviors that are usually vulnerable to be experienced by adolescents. However, in the application of Comprehensive Sexuality Education, there are several factors that are quite important, namely communication, knowledge and perception, unsafe sexual behavior and STI. Therefore it is recommended to the government to make Comprehensive Sexuality Education into a curriculum in secondary schools. So that in everyday life the application of comprehensive sexuality education can be easily understood by the adolescent who are students in secondary school.